Impacts of anthropogenic pressures on the contemporary biogeography of threatened crocodilians in Indonesia. Issue 3 (10th November 2017) - Shaney, Kyle J.; Hamidy, Amir; Walsh, Matthew; Arida, Evy; Arimbi, Aisyah; Smith, Eric N.
Abstract: The Greater Sunda region of South-east Asia supports a rich diversity of economically and ecologically important species. However, human pressures are reshaping contemporary biogeography across the region. Megafaunal distributional patterns have been particularly affected because of deforestation, poaching and human–wildlife conflict. Crocodilians are at the centre of these conflicts in Indonesia and yet remain poorly studied across much of the archipelago. We conducted population surveys of salt-water crocodiles Crocodylus porosus and false gharials Tomistoma schlegelii in Sumatra, and examined whether crocodile abundance and distribution are correlated with variations in human disturbance, fishing pressure, and habitat type. We then used these data to model remaining suitable habitat for T. schlegelii across South-east Asia. We found that abundance of T. schlegelii and C. porosus was correlated with distance from human settlements, and fish-trapping pressure. We recorded the presence of T. schlegelii in a river system in which it was previously unknown, thus expanding the known range of the species. We also found that the predicted remaining suitable habitat for T. schlegelii in Indonesia is largely limited to areas of low human activity. From these empirical and modelling approaches we propose several key conservation priorities: (1) eliminate the use of fish traps in remaining patches of T. schlegelii habitat, (2) prioritize crocodile population surveys in remaining suitable habitat, particularly in remote areas, (3) consider T. schlegelii to be potentially Endangered locally in Sumatra, and (4) expand existing reserves around the Lower Kampar River and Berbak National Park/Sembilang National Park areas of Sumatra.